Impact of CoCrFeNiMo High-Entropy-Alloy Doping on the Mechanical and Electrochemical Properties of B4C Ceramic - Rico-Cano, Alberto Daniel; Mirza-Rosca, Julia Claudia; Ocak, Burak Cagri; Goller, Gultekin (MDPI AG, 2025)
The purpose of this article is to evaluate and compare the mechanical and electro-chemical properties of four new materials, composed of a B4C ceramic matrix doped with 0.5%, 1%, 2% and 3% volumes of CoCrFeNiMo HEA with monolithic B4C. The studied samples were obtained using the spark plasma sintering technique. The structure and hardness of the samples were analyzed via scanning electron microscopy (SEM) and a Vickers microhardness test. After immersion in artificial sea water to simulate a corrosive marine environment, corrosion potential, corrosion rate and electrochemical impedance spectroscopy tests were carried out to determine the samples’ electrochemical behavior. Tafel slopes and the equivalent circuit that fit the EIS experimental data were obtained. A denser microstructure and smaller grain size was achieved as the HEA content increase. According to the Vickers measurements, every sample showed a normal distribution. All studied samples exhibit great corrosion resistance in a two-step chemical interaction, influenced by the presence of the Warburg element. The research demonstrates that increas- ing the HEA content implies better performance of corrosion resistance and mechanical properties, confirming the materials’ potential use in corrosive environments and harsh mechanical applications.
Keywords: boron carbide; ceramic; HEA; EIS; corrosion behavior; microhardness; SEM